2012
DOI: 10.1007/s10459-012-9374-z
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of heuristics and biases among pathologists in a computer-based system

Abstract: The purpose of this study is threefold: (1) to develop an automated, computer-based method to detect heuristics and biases as pathologists examine virtual slide cases, (2) to measure the frequency and distribution of heuristics and errors across three levels of training, and (3) to examine relationships of heuristics to biases, and biases to diagnostic errors. The authors conducted the study using a computer-based system to view and diagnose virtual slide cases. The software recorded participant responses thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 53 publications
(113 reference statements)
1
51
0
Order By: Relevance
“…This suggests that despite considerable experience, raters may still not possess well-developed fixed criteria against which to judge observed performance. 26 In other contexts such as clinical reasoning, experts have been shown to be just as susceptible to heuristics as novices, 27 which further supports this finding.…”
Section: Commentmentioning
confidence: 60%
“…This suggests that despite considerable experience, raters may still not possess well-developed fixed criteria against which to judge observed performance. 26 In other contexts such as clinical reasoning, experts have been shown to be just as susceptible to heuristics as novices, 27 which further supports this finding.…”
Section: Commentmentioning
confidence: 60%
“…Overall, at least one cognitive factor or bias was present in all studies. Studies evaluating more than two cognitive biases, found that 50 to 100 % of physicians were affected by at least one [39, 50, 52]. Only three manuscripts evaluated more than 5 cognitive biases in the same study, in-line with the narrow scope of most studies [39, 50, 52].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies comprising 6810 physicians (median 180 per study; range: 36–2206) met the inclusion criteria (Fig. 2) [30, 3452]. …”
Section: Resultsmentioning
confidence: 99%
“…Crowley et al (2013) created an instructional system to detect cognitive biases in clinical decision-making, while Coderre et al (2003) used protocol analysis on think-aloud diagnostic narratives, and found that features of intuitive reasoning implied diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%